Manajemen Kepemimpinan Dan Kemampuan Berkomunikasi Kepala Sekolah Pada Kinerja Pendidik - Abdul Rahmat; Syaiful Kadir (Jurnal Komunikasi, 2016)
AbstractThis research aims at ascertaining: (1) correlation between principal’s leadership and teachers’ performance, (2) correlation between principal’s communication capability and teachers’ performance, and (3) principal’s leadership and communication capability with teachers’ performance. Population of this research is 50 teachers. Sample of this research is all of members of population consisting 50 teachers (using total sampling technique). Data collecting is conducted by distributing questionaire to all respondents. Data analysis is done quantitaively by using statistical procedure with regression formula (Product Moment). Correlations Coefficients obtained from the result of testing hypothesis shows that: (1) hypothesis 1 is accepted, meaning that there are positive correlation between principal’s leadership and teachers’ performance, with correlations coefficients rxy = 0,64, categorized into significant correlation; (2) hypothesis 2 is accepted, meaning that there are positive correlation between principal’s communication capability and teachers’ performance, with correlations coefficients rxy = 0,78, categorized into significant correlation; and (3) hypothesis 3 is accepted, meaning that there are simultanously positive correlations among principal’s leadership and principal’s communication capability with teachers’ performance, with correlations coefficients ry.12= 0,86, categorized into very significant correlation.      AbstrakPenelitian ini bertujuan untuk mengetahui: (1) hubungan kepemimpinan kepala sekolah dengan kinerja pendidik, (2) hubungan  kemampuan berkomunikasi kepala sekolah dengan kinerja pendidik, dan (3) hubungan kepemimpinan kepala sekolah dan kemampuan berkomunikasi kepala sekolah dengan kinerja pendidik. Populasi penelitian ini sejumlah 50 orang. Sampel penelitian adalah sejumlah 50 orang. Pengumpulan data dilakukan dengan menggunakan kuesioner. Teknik analisis data dilakukan secara kuantitatif dengan uji statistik menggunakan rumus perhitungan regresi linier dan regresi berganda. Correlations Coefficients dari perhitungan statistik menunjukkan bahwa: (1) hipotesis pertama diterima, artinya terdapat hubungan hubungan kepemimpinan kepala sekolah dan kinerja pendidik, dengan hasil koefisien korelasi rxy = 0,64, dengan bentuk hubungan kuat; (2) hipotesis kedua diterima, artinya terdapat hubungan kemampuan berkomunikasi kepala sekolah dan kinerja pendidik, dengan hasil koefisien korelasi rxy = 0,78, dengan bentuk hubungan kuat; dan (3) hipotesis ketiga diterima, artinya terdapat hubungan kepemimpinan kepala sekolah dan kemampuan berkomunikasi kepala sekolah secara bersama-sama dengan kinerja pendidik dengan hasil koefisien korelasi ry.12= 0,86, dengan bentuk hubungan sangat kuat/tinggi.